Climatological Investigation of Ionospheric Es Layer Based on Occultation Data - Haibing Ruan; Xiuwen Qiu; Xin Guo; Xiangxue Wang; Xin Zhang (Remote Sensing)
Sporadic E (Es) layers are irregular structures that occur at the E-layer height of the ionosphere, significantly affecting the reliability and accuracy of wireless communications, navigation, and satellite remote sensing. This study utilized the S4max data collected from the Constellation Observing System for the Meteorology, Ionosphere, and Climate (COSMIC) occultation observations from 2007 to 2016 to identify the Es layer and investigate its climatological variations. The Horizontal Wind Field model (HWM14), in conjunction with the International Geomagnetic Reference Field model (IGRF13), is used to calculate vertical ion convergence (VIC) and analyze its correlation to the Es layers. The results of this study showed that the occurrence of Es has apparent hemispheric asymmetry. In the mid- and low latitudes, Es layer activity is more intense in the summer hemispheres, with center peak altitudes of around 105 km. The summer hemisphere exhibits a semi-diurnal periodic pattern, whereas the winter hemisphere shows a weakened diurnal variation. Simulation studies indicate that VIC induced by neutral wind shear contributes to the asymmetry in Es layer activities observed between the Northern and Southern hemispheres, and the zonal wind shear plays a more critical role than the meridional wind one.